2014
DOI: 10.1590/1516-3180.2014.1325669
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lower-limb muscle strength and functional independence among elderly people according to frailty criteria: a cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Muscle strength and functional independence are considered to be determinants of frailty levels among elderly people. The aim here was to compare lower-limb muscle strength (LLMS) with functional independence in relation to sex, age and number of frailty criteria, and to ascertain the influence of these variables on elderly outpatients' independence. DESIGN AND SETTING: Quantitative cross-sectional study, in a tertiary hospital. METHODS:The study was conducted on 150 elderly outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
4
15
1
2
Order By: Relevance
“…The statistically significant negative correlation between EI of the rectus femoris muscle and MS agrees with previously published data . These results lend credence to the observations of the researchers mentioned above, but to the knowledge of the authors, this is the first time that EI has been used to assess skeletal muscle in the clinical context of frailty …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The statistically significant negative correlation between EI of the rectus femoris muscle and MS agrees with previously published data . These results lend credence to the observations of the researchers mentioned above, but to the knowledge of the authors, this is the first time that EI has been used to assess skeletal muscle in the clinical context of frailty …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, unlike MS, EI is independent of sex, so the same limits are valid for both sexes. Although there are no other studies to support these findings, the fact that other variables such as MS, MT, and quality of life whose relationships with frailty have been established are significantly correlated with EI allows one to infer a correlation between EI and frailty.…”
Section: Discussionmentioning
confidence: 97%
“…The values found with better functional ability, for both lower and upper limbs, in the present study, differ from population studies undertaken with older adults in the community (26). The justification for our results may result from the effect of the healthy work, which is manifested mainly through greater independence and physical mobility.…”
Section: Discussioncontrasting
confidence: 94%
“…In line with this, previous studies by other authors have found that frailty status or severity to be associated with changes in the neural and musculoskeletal systems, amongst others, that are critically involved in postural control. 25,37,38,60,61 To the best of our knowledge, no other study, up until now, has provided evidence comparing postural sway parameters in relation to several different major measures of frailty, in parallel, in older individuals.…”
Section: Discussionmentioning
confidence: 99%